Pengaruh model teams games tournament berbantuan media question card terhadap pemahaman konsep bangun ruang - Agitha Anggraeni Putri; Tria Mardiana; Sukma Wijayanto (Universitas Muhammadiyah Magelang, 2022)
This study aims to determine the effect of the Model Teams Games Tournament (TGT) assisted by Question Card media on the understanding of the concept of building space for fifth grade students at SD Negeri Deyangan 2, Mertoyudan District, Magelang Regency. This study uses a Pre-Experimental Design research type with the One Group Pre-test Post-test Design model. Research subjects were selected by non-probability sampling saturated sampling model. Samples were taken as many as 18 students. by using the data collection method in the form of a description test of 10 questions. The validity test for the description of the ability to understand concepts used the shapiro wild formula with the help of IBM SPSS 25. In addition, the researchers used the level of difficulty test and the test of discriminating power. Data analysis used a non-parametric statistical technique, namely the Wilcoxon test. The results showed that the calculation of the average score of the post-test description test was 66.5 which was greater than the test results in the pre-test with an average value of 41.9. This is evidenced by the results of the Wilcoxon test analysis which shows Zcount of -0.3727 with a significance value of 0.00 <0.05, meaning that there is a significant difference between the results of the pre-test and post-test using the Teams Games Tournament (TGT) model assisted Media Question Card. The results of this study can be concluded that the use of the Model Teams Games Tournament (TGT) assisted by Question Card media has a significant effect on understanding the concept of flat shape.